ปัจจัยทำนายความพึงพอใจในงาน ของพยาบาลวิชาชีพ โรงพยาบาลทั่วไป สังกัดกระทรวงสาธารณสุข - ธนิต ไม้หอม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this study were to investigate job satisfaction professional nurse; the relationships between empowerment, ethical work climate, adversity quotient, and job satisfaction, and to examine the factor predicting job satisfaction of professional nurse, general hospital under jurisdiction of the ministry of public health. The research subjects, randomly selected through multi-stage sampling technique, The 19 districts across the country. consisted of 378 of professional nurse. An instrument as developed by the researcher which has been tested for content validity and reliability with Cronbach alpha coefficient of .93. Data were analyzed by using mean, standard deviation and stepwise multiple regression analysis. The major findings were as follow : 1. Job satisfaction of professional nurse was at moderate level. ( X = 3.36) 2. Empowerment, ethical work climate and adversity quotient were significantly related to job satisfaction of professional nurse, at .05 level (r=.624, .705 and .104, respectively) 3. Factor significantly predicted Job satisfaction of professional nurse were ethical work climate and empowerment, at .05 level. These predictors were accounted for 56.3 percent of variance (R2 = .563). The standardized equation was as follow : Job satisfaction = .517(Ethical work climate) + .274 (Empowerment)